2008
DOI: 10.1074/jbc.m708033200
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome-associated Coronavirus Nucleocapsid Protein Interacts with Smad3 and Modulates Transforming Growth Factor-β Signaling

Abstract: Severe acute respiratory syndrome (SARS) is an acute infectious disease with significant mortality. A typical clinical feature associated with SARS is pulmonary fibrosis and the associated lung failure. However, the underlying mechanism remains elusive. In this study, we demonstrate that SARS-associated coronavirus (SARS-CoV) nucleocapsid (N) protein potentiates transforming growth factor-␤ (TGF-␤)-induced expression of plasminogen activator inhibitor-1 but attenuates Smad3/ Smad4-mediated apoptosis of human p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
181
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(192 citation statements)
references
References 54 publications
6
181
0
5
Order By: Relevance
“…Examples include hepatitis B virus pX; hepatitis C virus core protein, NS3 and NS5; Kaposi sarcoma-associated herpesvirus K-bZIP; Epstein-Barr virus LMP1; and severe acute respiratory syndrome-associated coronavirus N protein. [39][40][41][42][43][44] Like HBZ, the HBV pX and severe acute respiratory syndrome N protein enhance the transcriptional responses of TGF-␤. The common strategy used by viruses to modulate TGF-␤ signaling is the direct binding of viral proteins to Smad proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include hepatitis B virus pX; hepatitis C virus core protein, NS3 and NS5; Kaposi sarcoma-associated herpesvirus K-bZIP; Epstein-Barr virus LMP1; and severe acute respiratory syndrome-associated coronavirus N protein. [39][40][41][42][43][44] Like HBZ, the HBV pX and severe acute respiratory syndrome N protein enhance the transcriptional responses of TGF-␤. The common strategy used by viruses to modulate TGF-␤ signaling is the direct binding of viral proteins to Smad proteins.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence showing that Smad4 is not indispensable for the development of the mammary gland, liver, or pancreas in mice [2,8]. We have demonstrated that the nucleocapsid (N) protein of severe acute respiratory syndromeassociated coronavirus can bind to Smad3, interfere with the complex formation between Smad3 and Smad4, and promote Smad3-p300 complex formation in the nucleus [9], indicating a novel mode of Smad3 effect in a Smad4-independent manner. TIF1g is also found to selectively associate with phosphorylated Smad2/3 in hematopoietic, mesenchymal, and epithelial cells in response to TGF-b and transduce the signal independent of Smad4 to promote erythrogenesis [10].…”
Section: Overview Of Tgf-b Signaling Pathwaysmentioning
confidence: 98%
“…We designed a point mutation of the catalytic site (MTMR4-C407S) in which the invariant cysteine residue in the CSDGWDR motif (present within all enzymatically active members of the MTMR superfamily (18)) was substituted by a serine residue by mutation using the QuickChange method (Promega). The various truncations of pCMV-MycSmad3 (pCMV-Myc-MH1, pCMV-Myc-MH1-Linker, pCMVMyc-MH2, pCMV-Myc-Linker-MH2), constitutively active Smad3 plasmid (pRK5-HA-Smad3 (SD)), and constitutively active T␤RI plasmid (pCS2-GGD-HA) used here have been described previously (21). pDsRed2-N1-EEA1 was constructed by subcloning EEA1 cDNA (provided by Dr. X.-J.…”
Section: Methodsmentioning
confidence: 99%